Sumbangan Dana Kampanye Pada Pemilu 2024 (Analisis Regulasi Kepemiluan di Indonesia) - Ilham Ilham; Irham Bashori Hasba (LPPM Universitas Ekasakti Padang, 2023)
The implementation of general elections in Indonesia requires a consistent and sustainable electoral system in order to minimize changes in new laws or regulations in each election. General elections as a key element of democratic implementation which involves direct participation of citizens in the election of state and government administrators. Democracy and elections have a close relationship because elections are a means to achieve democracy and oversee the process of transferring people's power to their representatives through political candidates. Elections are governed by constitutional principles and in accordance with the direction of state policy, one of which is through financial support by the state in elections and election participants. The implementation of campaigns by election participants definitely requires sources of funds obtained and derived from various sources based on applicable legal provisions and restrictions. The existence of Law Number 7 of 2017 concerning General Elections which also regulates campaign finance aims to ensure the achievement of fairness and transparency. Campaign finance limits apply of course with strict mechanisms because election finance often intersects with issues of transparency, accountability, money politics, corruption risks and resistance to politicization. Therefore, strict regulation and effective monitoring are needed. This study analyses election regulations in Indonesia with a focus on campaign finance. The juridical-normative approach is used to understand the written law and its implementation in practice. Data analysis is descriptive qualitative which aims to understand the dynamics of the use and important role of campaign funds in organizing general elections.